Ice & mixed climbing : improve technique, safety, and performance - Gadd, Will, 1967- (Mountaineers outdoor expert series., 2025)
"This comprehensive, deeply revised second edition of Ice & Mixed Climbing offers aspiring and experienced climbers alike the inspirational stories and cutting-edge insights that have made Will Gadd one of the most sought-after instructors in the world." --Back cover.